People's Republic of China : Staff Report for the 2004 Article IV Consultation. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2004)
This 2004 Article IV Consultation highlights that China has continued its rapid economic growth and integration into the global economy. Real GDP grew by 9.1 percent in 2003, underpinned by strong fixed investment and exports, which registered growth rates of 20 percent and 29 percent in real terms, respectively. Consumption growth declined somewhat from 2002, reflecting the impact of the SARS epidemic in the second quarter. Significant progress has been made in structural reforms. In the banking sector, restructuring plans are being put in place for the two state banks that were recently recapitalized.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet